Targeted knockout of GABA-A receptor gamma 2 subunit provokes transient light-induced reflex seizures in zebrafish larvae - Meijiang Liao; Uday Kundap; Richard E. Rosch; Dominic R. W. Burrows; Martin P. Meyer; Bouchra Ouled Amar Bencheikh; Patrick Cossette; Éric Samarut (The Company of Biologists, 2019)
Epilepsy is a common primary neurological disorder characterized by the chronic tendency of a patient to experience epileptic seizures, which are abnormal body movements or cognitive states that result from excessive, hypersynchronous brain activity. Epilepsy has been found to have numerous etiologies and, although about two-thirds of epilepsies were classically considered idiopathic, the majority of those are now believed to be of genetic origin. Mutations in genes involved in gamma-aminobutyric acid (GABA)-mediated inhibitory neurotransmission have been associated with a broad range of epilepsy syndromes. Mutations in the GABA-A receptor gamma 2 subunit gene (GABRG2), for example, have been associated with absence epilepsy and febrile seizures in humans. Several rodent models of GABRG2 loss of function depict clinical features of the disease; however, alternative genetic models more amenable for the study of ictogenesis and for high-throughput screening purposes are still needed. In this context, we generated a gabrg2 knockout (KO) zebrafish model (which we called R23X) that displayed light/dark-induced reflex seizures. Through high-resolution in vivo calcium imaging of the brain, we showed that this phenotype is associated with widespread increases in neuronal activity that can be effectively alleviated by the anti-epileptic drug valproic acid. Moreover, these seizures only occur at the larval stages but disappear after 1 week of age. Interestingly, our whole-transcriptome analysis showed that gabrg2 KO does not alter the expression of genes in the larval brain. As a result, the gabrg2−/− zebrafish is a novel in vivo genetic model of early epilepsies that opens new doors to investigate ictogenesis and for further drug-screening assays.